Parental educational attainment and adult offspring personality An intergenerational life span approach to the origin of adult personality traits.. [article]. - Sutin, Angelina R.; Luchetti, Martina
Why do some individuals have more self-control or are more vulnerable to stress than others? Where do these basic personality traits come from? Although a fundamental question in personality, more is known about how traits are related to important life outcomes than their developmental origins. The present research took an intergenerational life span approach to address whether a significant aspect of the childhood environment?parental educational attainment?was associated with offspring personality traits in adulthood. We tested the association between parents? educational levels and adult offspring personality traits in 7 samples (overall age range 14?95) and meta-analytically combined the results (total N > 60,000). Parents with more years of education had children who were more open, extraverted, and emotionally stable as adults. These associations were small but consistent, of similar modest magnitude to the association between life events and change in personality in adulthood, and were also supported by longitudinal analyses. Contrary to expectations, parental educational attainment was unrelated to offspring Conscientiousness, except for a surprisingly negative association in the younger cohorts. The results were similar in a subsample of participants who were adopted, which suggested that environmental mechanisms were as relevant as shared genetic variants. Participant levels of education were associated with greater conscientiousness, emotional stability, extraversion, and openness and partially mediated the relation between parent education and personality. Child IQ and family income were also partial mediators. The results of this research suggest that parental educational attainment is 1 intergenerational factor associated with offspring personality development in adulthood. -- (from the authors)